Professionalism is the Key to Create Public Value - Sami, Abdul; Jusoh, Ahmad; Md Nor, Khalil; Irfan, Asmara; Irum, Sobia; Imran Qureshi, Muhammad; Ishfaq, Muhammad (International Journal of Engineering and Technology, 2018)
Public value is a new and important concept in the public management research. This concept give a new idea of public management with theme of peoples first approach to facilitate them. Public value creation is the main concern of public mangers in todayâ€™s public sector organizations. Public value is based on three building blocks of public value that are services, trust and social outcome. Professionalism is an esential requirement to achieve these building blocks of public value. A professional public manager by virtue of his possition will be in a better position to create public value. The important attributes of a professional public manger includes honesty, competency, accountability, self regulation and specialized knowledge of his field and duties. These attributes of public managers will create public value and ultimately establish the trust of public on the organization and as a result, the country will become a welfare state.Â